(8y-7x)(8y+7x)=

Simple and best practice solution for (8y-7x)(8y+7x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8y-7x)(8y+7x)= equation:


Simplifying
(8y + -7x)(8y + 7x) = 0

Reorder the terms:
(-7x + 8y)(8y + 7x) = 0

Reorder the terms:
(-7x + 8y)(7x + 8y) = 0

Multiply (-7x + 8y) * (7x + 8y)
(-7x * (7x + 8y) + 8y * (7x + 8y)) = 0
((7x * -7x + 8y * -7x) + 8y * (7x + 8y)) = 0

Reorder the terms:
((-56xy + -49x2) + 8y * (7x + 8y)) = 0
((-56xy + -49x2) + 8y * (7x + 8y)) = 0
(-56xy + -49x2 + (7x * 8y + 8y * 8y)) = 0
(-56xy + -49x2 + (56xy + 64y2)) = 0

Reorder the terms:
(-56xy + 56xy + -49x2 + 64y2) = 0

Combine like terms: -56xy + 56xy = 0
(0 + -49x2 + 64y2) = 0
(-49x2 + 64y2) = 0

Solving
-49x2 + 64y2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-64y2' to each side of the equation.
-49x2 + 64y2 + -64y2 = 0 + -64y2

Combine like terms: 64y2 + -64y2 = 0
-49x2 + 0 = 0 + -64y2
-49x2 = 0 + -64y2
Remove the zero:
-49x2 = -64y2

Divide each side by '-49'.
x2 = 1.306122449y2

Simplifying
x2 = 1.306122449y2

Take the square root of each side:
x = {-1.142857143y, 1.142857143y}

See similar equations:

| 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 | | 10-3t=4 | | 0.2b+9=0.5b+18 | | 3x*6=39 | | -2v(v-5)(v-6)=0 | | 7x(8-2)= | | 11k-5=9k+7 | | 11-46=n | | -3(4y-4)=2(1-7y)+11 | | 2ln(x)=21 | | 3k-5-10k=23-1k | | -2x-2=-6-2 | | 5+2(4x-3)= | | 3x(x+4)-4=2(x+4)+x | | 19.03-12.9h=-14h | | 4x-7-3+2x=8 | | -(3y-6)+4(5y-8)=8 | | -13y+7+9=-10y-11 | | 9(x+3)-5x-3(5+3x)= | | 0.5n-18=-4 | | -q+17=-2q | | 17c-9=18c-19 | | c/8=41 | | -7+3=-5b+17 | | 2(3x-5x)=4x+12 | | 12n+15=11n | | -16+9-15g=1-11g | | -10+9m+3=m+9 | | 6p=15+7p | | r+3/5=4 |

Equations solver categories